Perceived academic anxiety and procrastination among emergency nursing students: the mediating role of cognitive emotion regulation - Amina Hemida Salem Ghattas; Ayman Mohamed El-Ashry (BMC, 2024)
Abstract Aim Explore the mediating role of cognitive emotion regulation strategies used by nursing students between academic anxiety and procrastination. Design: A descriptive correlational design was used. Setting: This study was carried out in the faculty of nursing at the University of Alexandria. Sample: The participants in this study were all students enrolled in emergency nursing during the second semester of the academic year 2021-2022 and a convenience sampling of 654 nursing students. The Sobel test was used as a statistical method to determine the significance of a mediation effect by assessing whether the relationship between perceived academic anxiety and procrastination was significantly reduced when cognitive emotion regulation was included, using coefficients and standard errors from regression models to calculate the test statistic. Tools: Academic Anxiety Scale, Academic Procrastination Scale, and Cognitive Emotion Regulation Questionnaire were used to collect data. Results The study found that 46.5% of students reported high anxiety levels, with 40.1% perceiving moderate anxiety and only 11.3% experiencing low anxiety. Moreover, 80.4% of nursing students showed moderate academic procrastination. There is a positive correlation between procrastination and academic anxiety, with Adaptive and maladaptive coping strategies mediating this relationship, according to the Sobel test. Conclusion Based on the results, it can be concluded that there is a complex causal and effect relationship between academic anxiety and procrastination. Nursing students may resort to academic procrastination as a means of coping. Therefore, reducing anxiety, correcting maladaptive behaviors, and enhancing adaptive cognitive and emotional regulation strategies could effectively reduce academic procrastination.